The Effect of Oral Chitosan Supplementation on Leptin Levels and HOMA-IR in Male Wistar Rats (Rattus norvegicus) with an Obesity Model - Lidwina Stefani; I Made Pande Dwipayana; Ida Ayu Alit Widhiartini; Desak Made Wihandani; I Putu Bayu Mayura (Eduvest - Journal of Universal Studies, 2025)
This study investigates the role of chitosan in modulating leptin and insulin levels, key hormones involved in metabolic disorders, and compares its effectiveness with orlistat, a commonly used anti-obesity drug. An experimental post-test only group design was used involving 20 healthy male Wistar rats aged 3–4 months. After a seven-day acclimation, obesity was induced through a high-fat, high-glucose diet. The rats were then divided into five groups: a positive control group (K+) receiving orlistat, a negative control (K−) receiving a standard diet, and three treatment groups receiving chitosan at 2.5% (P1), 5% (P2), and 7.5% (P3) concentrations, respectively, for 14 days. Leptin and HOMA-IR levels were measured via blood samples collected from the retro-orbital sinus. The Kruskal-Wallis test showed significant differences among groups (p<0.05). Mean leptin levels were highest in K− (5.10±0.35 ng/dL) and lowest in K+ (3.03±0.71 ng/dL), while P2 showed a notable reduction (3.71±0.32 ng/dL). HOMA-IR levels followed a similar trend, with the lowest in K+ (1.00±0.08) and significantly reduced in P2 (1.34±0.11) compared to K− (2.29±0.25). Post Hoc analysis confirmed that P2 had significantly better outcomes than K−, though not as effective as orlistat. In conclusion, chitosan—particularly at 5% concentration—can reduce leptin and HOMA-IR levels, improving insulin resistance in obesity, though orlistat remains more effective.